Phytochemical study, an evaluation of the antioxidant potential and the antimicrobial activity of Inga semialata (Vell.) C. Mart. hydroalcohol extract. Issue 1 (2nd January 2020) - Maziero, Maiara; Lovatto, Marina Ortiz; Lorenzoni, Vinícius Victor; Moraes, Greice Graziela; Dornelles, Rafaela Castro; Sagrillo, Michele Rorato; Horner, Rosmari; Manfron, Melânia Palermo
Abstract: Inga semialata (Vell.) C. Mart. belongs to the family Fabaceae. It is known for its therapeutic properties, highlighting its antimicrobial and antioxidant potential. The objective of the present work was to obtain crude extract leaves of Inga semialata, to identify and quantify active compounds, to evaluate the antioxidant potential of the crude extract in vitro, as well as to determine its antimicrobial activity. The crude extract was obtained by the maceration process. The identified and quantified of compounds present in the crude extract of Inga semialata was performed by high performance liquid chromatography. The evaluation of the antioxidant potential of the extract was realized by in vitro tests (DPPH, diacetate dichlorofluorescein test and nitric oxide test) and the evaluation of the antimicrobial activity was carried out using the minimum inhibitory concentration methodology. Abstract :